Women living with multi-morbidity in the Greater Accra Region of Ghana: a qualitative study guided by the Cumulative Complexity Model. Issue 4 (26th November 2018) - Morgan, Sara A.; Eyles, Caroline; Roderick, Paul J.; Adongo, Philip B.; Hill, Allan G.
Abstract: Defined as the co-occurrence of more than two chronic conditions, multi-morbidity has been described as a significant health care problem: a trend linked to a rise in non-communicable disease and an ageing population. Evidence on the experiences of living with multi-morbidity in middle-income countries (MICs) is limited. In high-income countries (HICs), multi-morbidity has a complex impact on health outcomes, including functional status, disability and quality of life, complexity of health care and burden of treatment. Previous evidence also shows that multi-morbidity is consistently higher amongst women. This study aimed to explore the perceptions and experiences of women living with multi-morbidity in the Greater Accra Region, Ghana: to understand the complexity of their health needs due to multi-morbidity, and to document how the health system has responded. Guided by the Cumulative Complexity Model, and using stratified purposive sampling, 20 in-depth interviews were conducted between May and September 2015 across three polyclinics in the Greater Accra Region. The data were analysed using the six phases of Thematic Analysis. Overall four themes emerged: 1) the influences on patients' health experience; 2) seeking care and the responsiveness of the health care system; 3) how patients manage health care demands; and 4) outcomes due to health. Spirituality and the stigmatization caused by specific conditions, such as HIV, impacted their overall health experience. Women depended on the care and treatment provided through the health care system despite inconsistent coverage and a lack of choice thereof, although their experiences varied by chronic condition. Women depended on their family and community to offset the financial burden of treatment costs, which was exacerbated by having many conditions. The implications are that integrated health and social support, such as streamlining procedures and professional training on managing complexity, would benefit and reduce the burden of multi-morbidity experienced by women with multi-morbidity in Ghana.